Investigations on AlN/sapphire piezoelectric bilayer structure for high-temperature SAW applications - Aubert, Thierry (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2012)
This paper explores the possibility of using AlN/sapphire piezoelectric bilayer structures for high-temperature SAW applications. To determine the temperature stability of AlN, homemade AlN/sapphire samples are annealed in air atmosphere for 2 to 20 h at temperatures from 700 to 1000°C. Ex situ X-ray diffraction measurements reveal that the microstructure of the thin film is not affected by temperatures below 1000°C. Ellipsometry and secondary ion mass spectroscopy investigations attest that AlN/sapphire is reliable up to 700°C. Beyond this temperature, both methods indicate ongoing surface oxidation of AlN. Additionally, Pt/Ta and Al interdigital transducers are patterned on the surface of the AlN film. The resulting SAW devices are characterized up to 500°C and 300°C, respectively, showing reliable frequency response and a large, quasi-constant temperature sensitivity, with a first-order temperature coefficient of frequency around -75 ppm/°C. Between room temperature and 300°C, both electromechanical coupling coefficient K(2) and propagation losses increase, so the evolution of delay lines' insertion losses with temperature strongly depends on the length of the propagation path